Effect of filler on performance of porous asphalt pavement using multiscale finite element method. Issue 9 (29th July 2022) - Du, Cong; Lu, Guoyang; Wang, Haopeng; Sun, Yiren; Liu, Pengfei; Wang, Dawei; Leischner, Sabine; Oeser, Markus
ABSTRACT: Porous asphalt (PA) pavements are widely employed in areas with wet climates. As particle enhancement inclusions in asphalt mastic, mineral fillers play essential roles in improving the performance of PA pavements. This study developed a coupled multiscale finite element (FE) model, involving the mesostructure of PA mixture and PA pavement. Four types of mastic properties were employed with four mineral fillers (Granodiorite, Limestone, Dolomite, and Rhyolite) in the mesoscale portion of the pavement model to analyse the effects of filler types on the performance of pavements. The performances (load-bearing capacity, rutting resistance, and ravelling resistance) of pavements with different fillers were identified and ranked, and their correlations with the chemical components of the four fillers were analysed. The computational results showed that pavements with Rhyolite and Granodiorite fillers have higher load-bearing capacities and rutting resistance, while the Limestone and Dolomite fillers can improve the ravelling resistance of the PA pavements. In the correlation analysis, the chemical components Al2 O3 and SiO2 play dominant roles in improving the load-bearing capacities and rutting resistance of the PA pavements, and the fillers with high percentages of CaO can improve the ravelling resistance of the PA pavements. Highlights A coupled multiscale finite element model of porous asphalt pavement is established. The performances of PA pavements with four mineral fillers are simulated and ranked. The correlations between pavement performances and filler types are identified.